2016
DOI: 10.1038/pr.2016.66
|View full text |Cite
|
Sign up to set email alerts
|

Changes of the plasma metabolome of newly born piglets subjected to postnatal hypoxia and resuscitation with air

Abstract: Background: Perinatal hypoxic-ischemic brain damage is a major cause of mortality and morbidity in the neonatal period. Currently, limited ranges of biochemical tests assessing the intensity and duration of hypoxia are ready for clinical use. However, the need to initiate hypothermia therapy early after the clinical suspicion of hypoxic-ischemic encephalopathy requires the availability of early and reliable hypoxia markers. We have sought these biomarkers in an experimental model of hypoxia reoxygenation. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 29 publications
2
20
0
Order By: Relevance
“…Recent studies in hypoxic newborn piglets have demonstrated that severe hypoxia induces changes in specific metabolites in the plasma metabolome and that using a plasma metabolite score may improve predicting the severity of hypoxic insults, which could clinically help stratify patient treatment. [25, 26] Future experiments involving hypoxic animals should continue to study the plasma metabolome to gain further knowledge regarding the cellular alterations that occur during hypoxia to better target specific therapeutic interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in hypoxic newborn piglets have demonstrated that severe hypoxia induces changes in specific metabolites in the plasma metabolome and that using a plasma metabolite score may improve predicting the severity of hypoxic insults, which could clinically help stratify patient treatment. [25, 26] Future experiments involving hypoxic animals should continue to study the plasma metabolome to gain further knowledge regarding the cellular alterations that occur during hypoxia to better target specific therapeutic interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Several research papers were devoted to the study of the effect of asphyxia and resuscitation on the plasma metabolome of newborn piglets [30][31][32][33][34][35]. Solberg et al investigated the effect of hypoxemia of different durations (40-140 min) and resuscitation with different oxygenation regimens (100% oxygen, 100% followed by room air, or solely room air) in the plasma of newborn piglets by targeted LC-MS [30].…”
Section: Animal Modelsmentioning
confidence: 99%
“…Data presented in Table 1 demonstrate that physiological variables do not provide sufficient predictive capacity as they return to normal values during resuscitation. In this study we assessed and compared the evolution of four metabolites, namely choline, betaine, cytidine and uridine, which have been identified as potential biomarkers of hypoxia in previous studies13192021. Levels of lactate, which are currently considered the gold standard for assessing asphyxia in the clinics, were used throughout this work as reference for comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous surveillance of blood pressure, saturation, pulse, temperature, and blood gas measurements were performed. In this study both reoxygenation groups were merged together (intervention group, n = 26) as no statistically significant differences could be found between animals from both groups in a previous untarget metabolomics study19.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation